2008
DOI: 10.1590/s0034-72992008000300007
|View full text |Cite
|
Sign up to set email alerts
|

Achados otoneurológicos em pacientes com doença de Parkinson

Abstract: The number of elderly people is increasing considerably in our settings, and with that we have a matching increase in chronic-degenerative diseases -such as Parkinson's Disease (PD), which has balance-related symptoms associated and is increasingly more prevalent in the elderly population. Aim: Study labyrinth exams in PD patients and associate them with vestibular disorders. Study design: contemporary crosssectional cohort. Materials and Methods. Thirty patients were assessed, twenty females and ten males, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…As to the results of vectoelectronystagmograph, the biggest alterations are related to the research of postcaloric nystagmus, in which 5 (41.5%) of the patients had an altered result, 2 of whom (16.6%) were cases of directional prevalence. The findings of this study partially agree with BASSETO et al's reports (22), who found alterations in PD patients'' vestibular examination, which mostly occurred in the caloric test, however prevalently in the bilateral labyrinth hyporeflexia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As to the results of vectoelectronystagmograph, the biggest alterations are related to the research of postcaloric nystagmus, in which 5 (41.5%) of the patients had an altered result, 2 of whom (16.6%) were cases of directional prevalence. The findings of this study partially agree with BASSETO et al's reports (22), who found alterations in PD patients'' vestibular examination, which mostly occurred in the caloric test, however prevalently in the bilateral labyrinth hyporeflexia.…”
Section: Discussionsupporting
confidence: 93%
“…In the present research, among the 12 evaluated, 6 (50.0%) were found with an altered examination, and in a higher proportion the central vestibular syndrome. BASSETO et al (22), evaluating 30 PD patients, they observed the occurrence of nine cases of bilateral peripheral vestibular deficit syndrome; six cases of unilateral peripheral vestibular deficit syndrome; six cases of unilateral irritating peripheral vestibular syndrome; five cases of normal vestibular examination; two cases of bilateral irritating peripheral vestibular syndrome; one case of bilateral irritating central vestibular syndrome, and one case of bilateral central vestibular deficit syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In PD patients, we notice a higher prevalence of tinnitus, tremor, gait unbalance, risk of falling and dizziness. In this context, the peripheral vestibular system and also the caloric test showed alterations (Bassetto et al, 2008). Pedunculopontine nucleus-thalamic controls the postural sensory integration in PD patients.…”
Section: Resultsmentioning
confidence: 87%
“…A instabilidade postural é umas das principais queixas dos indivíduos com DP (BASSETO et. al., 2008;LAMÔNICA et.…”
Section: Instabilidade Postural Na Dpunclassified